2017
DOI: 10.5530/ijper.51.4s.106
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Evaluation of Cytotoxic Effect and Antioxidant Activity of Fractions Isolated from Stenochlaena palustri (Burm.f.) Bedd. Leaves

Abstract: Introduction: Stenochlaena palustris (Burm.f.) Bedd. is an edible fern from Blechnaceae family, native to India through Southeast Asia to Polynesia and Australia. The study was conducted to evaluate the cytotoxic effect and antioxidant activity of fractions obtained from Stenochlaena palustris leaf extracts. Methods: Stenochlaena palustris (Burm.f.) Bedd. was tested for its antioxidant activity using DPPH assay and in vitro cytotoxic effect against HeLa cancer cell line using MTT assay. Major fractions were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 7 publications
(8 reference statements)
1
14
0
Order By: Relevance
“…was known as antioxidant and antimicrobial, so it can be efficacious to cure wound. [21][22] Various studies reported that Annona muricata L., Morinda citrifolia L., and Phaleria macrocarpa (Scheff.) Boerl.…”
Section: Resultsmentioning
confidence: 99%
“…was known as antioxidant and antimicrobial, so it can be efficacious to cure wound. [21][22] Various studies reported that Annona muricata L., Morinda citrifolia L., and Phaleria macrocarpa (Scheff.) Boerl.…”
Section: Resultsmentioning
confidence: 99%
“…Ethyl acetate is known to dissolve alkaloids, polyphenols, tannins, flavonoids, terpenes, steroids, and quinones (Gangula et al, 2013;Mustarichie et al, 2017). The ethyl acetate S. palustris extract also contained high amounts of alkaloids, flavonoids, phenols, and saponins, moderate amounts of terpenoids, and a low number of glycosides and tannins (Arullappan et al, 2017;Saragih et al, 2017).…”
Section: Principal Component Isolationmentioning
confidence: 99%
“…Diplazium esculentum Retz., from the family Athyriaceae and Stenochlaena palustris , from the family Blechnaceae, are edible ferns commonly found abundant in areas such as Southeast Asia (Badola, 2010; Chambers, 2013). Both grow in an open wet undisturbed environment (Arullappan et al, 2017; Cambie & Ash, 1994) and hold an economical value where they are sold in markets to be consumed. Apart from their edible nature, both species are also believed to have medicinal values.…”
Section: Introductionmentioning
confidence: 99%